Strategi manajemen risiko pembiayaan dalam perbankan syariah: studi terhadap risiko pembiayaan dan upaya mitigasinya - arifah, kamelia nurul (Maliki Interdisciplinary Journal, 2025)
Financing risk management is a crucial aspect in maintaining the stability and sustainability of Islamic banking operations. This article aims to examine the common types of financing risks faced by Islamic banks, as well as the mitigation strategies implemented to reduce potential losses. The method used in this article is a literature review with a qualitative descriptive approach, referring to five scientific journals published between 2020 and 2024. The study results indicate that financing risks arise from internal factors such as weaknesses in financing analysis and organizational structure, as well as external factors like exchange rate fluctuations, inflation, and macroeconomic conditions. Risk mitigation strategies include the application of the 5C analysis, utilization of information systems such as SIGMA, human resource training, and supervision by the Sharia Supervisory Board. A case study at Bank Syariah Mandiri demonstrates that the implementation of structured mitigation strategies aligned with Sharia principles can effectively reduce the risk of Non-Performing Financing (NPF). Therefore, financing risk management in Islamic banking must be based on prudence principles, technological innovation, and adherence to Sharia values.